Review of Applications of Ground Penetrating Radar as an NDT Tool - Pandharpatte Priyanka A.; Adake Ashutosh D.; Sapkal Neha R; M. M. Maske (Universitas Pendidikan Indonesia (UPI), 2022)
Ground-penetrating radar (also referred to as GPR, ground probing radar, or georadar) is a near-surface geophysical tool with a wide range of applications. Over the past 30 years, GPR has been used successfully to aid in constraining problems in diverse fields such as archaeology, environmental site characterization, glaciology, hydrology, land mine/unexploded ordinance detection, sedimentology, and structural geology. In many cases, however, GPR surveys have been planned or executed with little or no understanding of the physical basis by which GPR operates and is constrained. As a result, many unsuccessful GPR studies have also been presented or published over the past 30 years. The objectives of this primer are to (1) provide an introduction to the important variables pertinent to GPR and (2) explain the relevant aspects of these variables in GPR acquisition, in an attempt to provide fundamental knowledge for improving GPR usage in the future.